The caring heirs of Doctor Samuel Bard : profiles of selected distinguished graduates of Columbia University Vagelos College of Physicians and Surgeons - Wortsman, Peter (Columbiana., 2019)
Peter Wortsman offers a selection of profiles of Columbia-educated doctors who have made a fundamental difference in the lives of others. The physicians profiled in this book represent the complete spectrum of MDs.